Evaluation of the effects of donepezil in psychotic disorders using Swiss albino mice - Tanwani, Hemant; Churihar, Ritesh; Pandit, Sameer (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Schizophrenia as a psychotic disorder is currently treated by various antipsychotic drugs. A large group of patients still remain resistant to the treatment and present in the form of residual cognitive deficits. Donepezil has been advocated at various conferences and seminars for using it in schizophrenia patients. Donepezil is currently approved drug for Alzheimer’s disease to improve cognition. Hence, we have tried to assess its role for psychotic models induced by methylphenidate in mice. Methods: Methylphenidate 5 mg/kg was given by intraperitoneal (i.p) route to induce psychosis in Swiss albino mice (n=6). Donepezil was given alone in a dose of 1 mg/kg and in combination with low dose haloperidol 0.1 mg/kg and groups were compared with haloperidol 0.2 mg/kg. Activity of donepezil was also assessed on the haloperidol induced catalepsy test. Statistical analysis was done with ANOVA followed by Bonferroni’s test. Results: Methylphenidate successfully induced characteristic stereotypy behaviour in mice similar to amphetamine. Both donepezil 1 mg/kg and haloperidol 0.2 mg/kg showed significant reduction in stereotypy behaviour and there was no statistically significant difference between the two (p<0.05). Effects with donepezil were only slightly inferior to standard while it’s combination (1 mg/kg with haloperidol 0.1 mg/kg) showed comparable results with the standard haloperidol. Donepezil had only marginally enhanced potential to induce catatonia which was statistically insignificant (p>0.05). Conclusions: Methylphenidate can be used successfully to induce psychosis in animals and donepezil may be a promising and potentially useful drug as add on therapy to routine antipsychotics.